Research on Parameter Sensitivity of Reasoning Formula Based on Error Principle - ZHOU Bin (Renmin Zhujiang)
The reasoning formula for calculating rainstorm and flood is widely used in China, andthe error of its original parameters will lead to the calculation error of surface runoff peakvalue. The relative error propagation equation of the first-order algebraic precision of eachoriginal parameter can be obtained by expanding the basic equation of reasoning formula with thefirst-order Taylor formula of multivariate function. The results show that: Under the conditionof local runoff generation, the relative error propagation effect of the total rainstorm amount isthe strongest and enlarged, that of the confluence parameters, basin area and main river length isapproximately equivalent and 3 times of the weighted average slope, and that of the infiltrationamount is closely related to the ratio of it to the surface runoff. Under the condition offull-scale runoff generation, the relative error propagation effect of confluence parameters andmain river length is equivalent and 3 times of the weighted average slope, and that of eachoriginal parameter also varies with the rainstorm attenuation index and the ratio of infiltrationamount to surface runoff. The research conclusion is helpful for screening the highly sensitiveparameters that affect the precision of flood results and guiding the review calibration of thesehighly sensitive parameters to improve the precision of flood calculation.